The Role of Baturraden Lokawisata Destination in Increasing Income and SocioEconomic Welfare of the Baturraden Community - Fakhira, Aqila Ananta; Savirra, Dicoprilla Mutiara; Rahayu, Dijan; Anggraeni, Oki (Edukasi IPS, 2025)
This study aims to determine the effect of Baturraden Lokawisata on increasing income and socio-economic welfare for the surrounding community. Using a qualitative approach. The results showed that Baturraden Lokawisata became the main source of income for the local community. The income earned is used to fulfill daily needs, finance children's education, and other household needs. In addition to the economic impact, there is also a harmonious social relationship between locawisata managers. However, some respondents complained about the decline in income and hoped for innovation from tourism managers. Baturraden Tourism is proven to make a real contribution to the economic and social welfare of the community, but still requires development so that the benefits are more optimal.